Liquid metal fiber based on wet spinning and preparation method thereof
Liquid metal fibers are prepared by wet spinning process, and the combination of polymer elastomer and solid conductive substances is used to solve the flowability and conductivity problems of liquid metal fibers, achieving efficient and stable fiber preparation and application.
Patent Information
- Application Number
- CN202510069488.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
The existing liquid metal fiber preparation technology faces problems such as leakage caused by high fluidity, complex packaging process affecting application efficiency, and high difficulty in fibrosis preparation.
The core sheath fibers were prepared by wet spinning process, and liquid metal fibers were obtained by thermal insulation annealing. The sheath layer of the core sheath fiber is composed of polymer elastomer I, which is composed of liquid metal, solid conductive substance and polymer elastomer II. By adjusting the composition and process parameters in the spinning liquid, the flowability and conductivity of the liquid metal are controlled.
The stability and conductivity of liquid metal fibers are improved, the leakage of liquid metals is avoided, the packaging process is simplified, and the spinning and application efficiency of fibers is improved.
Smart Images

Figure CN119877148A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of intelligent clothing and relates to a liquid metal fiber based on wet spinning and a preparation method thereof. Background Art
[0002] With the rapid development of wearable devices, smart clothing and flexible electronic devices, the demand for conductive fibers that are both conductive, flexible and durable has increased rapidly. Conductive fibers are key components of these devices and need to have good conductivity and be able to maintain stability under dynamic stress conditions such as stretching and bending. Traditional metal wires have good conductivity, but their rigidity and brittleness make them easy to break when bent or stretched, making them unsuitable for the needs of the flexible electronics field.
[0003] Conductive fibers formed by the composite of conductive particles and flexible polymers have both certain flexibility and conductivity. However, their disadvantages are: conductive particles can only form a continuous conductive path when the percolation threshold is reached; stretching or bending may destroy the contact between conductive particles, resulting in a decrease in conductivity; although high filling amount of conductive particles can improve conductivity, it will reduce the flexibility of the material. In multiple stretching cycles, the conductive network is prone to breakage or degradation, resulting in conductivity attenuation.
[0004] Liquid metal is a material with unique physical and chemical properties. It usually refers to metals or metal alloys that are liquid at room temperature or near room temperature, such as gallium-based, indium-based and tin-based alloys. Liquid metal has broad application prospects in flexible electronics, sensors, energy devices and smart materials due to its low melting point, high electrical conductivity, high thermal conductivity and good fluidity. However, the fluidity and formability of liquid metal pose great challenges to its application in fiber structures.
[0005] Fiber materials have the characteristics of large specific surface area, good flexibility and easy weaving, and have attracted extensive attention in the fields of wearable electronic devices, flexible sensors and smart fabrics. The successful preparation of liquid metal fibers can combine the excellent properties of liquid metal with the flexible characteristics of fiber materials, significantly expanding the application scenarios of liquid metal. However, the current liquid metal fiber preparation technology still faces the following problems:
[0006] (1) Leakage problems caused by high mobility;
[0007] Liquid metal is in liquid state at room temperature or near room temperature, and its high fluidity makes it very easy to leak during use or processing. Such leakage not only reduces the reliability of the equipment, but also may cause environmental safety problems, limiting the popularity of liquid metal in practical applications.
[0008] (2) The packaging process is complex, affecting application efficiency;
[0009] To reduce the leakage of liquid metal, currently, multi-layer packaging structures or external protective materials are mostly used. However, these methods require additional process steps, which not only increases production costs, but also affects the flexibility and conductivity of the material.
[0010] (3) Fibrosis preparation is difficult;
[0011] In the prior art, liquid metal needs to be compounded with polymer materials to form a stable structure during the fiberization preparation process. However, due to the high fluidity and large surface tension of liquid metal, its compatibility with the matrix material is poor, resulting in a complex preparation process and a low yield.
[0012] There are many preparation processes for conductive fibers based on liquid metal materials, such as electrospinning, melt spinning, hollow injection, etc. For example, in patent CN202311681238.0, liquid metal fiber composite wires are prepared by electrospinning, and liquid metal fiber films with a connected three-dimensional network interwoven structure are further prepared, but this method cannot prepare a single liquid metal fiber and can only be presented in the form of a liquid metal film. Patent CN202110651134.X uses injection technology to achieve the infusion of liquid metal in hollow fibers, and uses chemical adhesives to strengthen the adhesion between liquid metal and hollow fibers, but the hollow injection method has a complicated process and cannot be prepared efficiently and continuously. Patent CN202210012360.8 uses a method of self-encapsulating organic polymer-coated liquid metal wires, and uses electrochemical in-situ polymerization to prepare linear liquid metal wires. This method requires a large amount of electrochemical coagulation bath energy consumption and has certain limitations. The wet-spun sheath-core structure liquid metal fiber of patent CN202410144146.7 focuses on the relationship between the diameter ratio of the circle formed by the liquid metal core layer and the circle formed by the elastic carrier layer. The diameter ratio mainly affects the conductive properties and the spinnability of the fiber, and does not involve the discussion of the fluidity of liquid metal. At the same time, under the action of external force, the conductive fiber cannot avoid sensor failure and safety problems caused by liquid metal leakage.
[0013] Therefore, it is of great significance to study a liquid metal fiber based on wet spinning and a preparation method thereof to solve the problems existing in the prior art. Summary of the invention
[0014] The purpose of the present invention is to solve the problems existing in the prior art and to provide a liquid metal fiber based on wet spinning and a preparation method thereof.
[0015] A method for preparing liquid metal fiber, using a wet spinning process to prepare core sheath fiber, and obtaining liquid metal fiber after heat preservation annealing;
[0016] In the core-sheath fiber, the raw material corresponding to the sheath layer is spinning solution I, and the raw material corresponding to the core layer is spinning solution II;
[0017] The spinning solution I is prepared by adding a polymer elastomer I into an organic solvent I;
[0018] The spinning solution II is prepared by adding liquid metal (LM), solid conductive material and polymer elastomer II into organic solvent II;
[0019] Based on the total mass of the liquid metal, the solid conductive material and the polymer elastomer II, the mass of the solid conductive material accounts for 1 to 7%, and the mass of the polymer elastomer II accounts for 5 to 11%;
[0020] The mass volume ratio of polymer elastomer II to organic solvent II is 200-400 mg:1 mL.
[0021] As the preferred technical solution:
[0022] The preparation method of the liquid metal fiber as described above, the specific steps of the preparation method are as follows:
[0023] (1) preparing spinning solution I;
[0024] Adding a polymer elastomer I into an organic solvent I and stirring until the polymer elastomer I is completely dissolved to obtain a spinning solution I;
[0025] (2) preparing spinning solution II;
[0026] Adding polymer elastomer II to organic solvent II, stirring until polymer elastomer II is completely dissolved to obtain solution A, and then adding liquid metal and solid conductive material to solution A to obtain spinning solution II;
[0027] (3) Liquid metal fibers are produced by coaxial wet spinning process;
[0028] Spinning solution I is used as the outer spinning solution, and spinning solution II is used as the inner spinning solution, and then the two are added into a syringe respectively, and the spinning solution I and the spinning solution II are pushed into a coagulation bath through a coaxial needle to obtain a primary fiber, and the primary fiber is sequentially drawn and wound by a winding device to obtain a core-sheath fiber, and finally the core-sheath fiber is placed in a vacuum oven for heat preservation annealing to obtain a liquid metal fiber;
[0029] The propulsion speed of the spinning solution I is 250-400 μm / min, and the propulsion speed of the spinning solution II is 60-150 μm / min; the draft ratio is 1-5:1; the annealing temperature is 50-80° C., and the annealing time is 8-15 hours.
[0030] In the method for preparing a liquid metal fiber as described above, the liquid metal is one or more of gallium, gallium-indium alloy and gallium-indium-tin alloy; the solid conductive material is one or more of a metal material and a carbon-based material; the metal material is one or more of silver nanoparticles, copper nanoparticles, silver nanowires, copper nanowires, silver nanosheets and copper nanosheets; and the carbon-based material is one or more of carbon black, carbon nanotubes and graphene.
[0031] In the preparation method of a liquid metal fiber as described above, the polymer elastomer I and the polymer elastomer II are each independently selected from one or more of acrylonitrile-butadiene-styrene copolymer (ABS), styrene-ethylene / butylene-styrene block copolymer (SEBS), thermoplastic polyurethane (TPU), thermoplastic polyester elastomer (TPPE), thermoplastic silicone elastomer (Geniomer) and styrene-butadiene-styrene block copolymer (SBS).
[0032] In the method for preparing a liquid metal fiber as described above, the organic solvent I and the organic solvent II are independently selected from one or more of acetone, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAC) and toluene; the coagulation bath is one or more of water, brine, methanol, ethanol, isopropanol, cyclohexane and hexane; and the brine is a 5wt% NaCl aqueous solution.
[0033] In the above-mentioned method for preparing liquid metal fiber, the mass ratio of polymer elastomer I to organic solvent I is 15-35:100.
[0034] In the preparation method of a liquid metal fiber as described above, the liquid metal needs to be crushed before being added to solution A. The specific process is: adding the liquid metal to the organic solvent III to obtain a mixed solution, ultrasonically treating the mixed solution for 40 to 80 minutes with an ultrasonic cell crusher, and then using a suction filtration device to remove the organic solvent III in the mixed solution after ultrasonication and retain the liquid metal after ultrasonication, and placing the liquid metal after ultrasonication in a vacuum oven at 100 to 150° C. for 9 to 15 hours to completely remove the residual organic solvent; the organic solvent III is one or more of acetone, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAC) and toluene.
[0035] As described above, a method for preparing liquid metal fiber is described, after adding liquid metal and solid conductive material to solution A, mixing and stirring and defoaming stirring are carried out in sequence; the mixing and stirring time is 90 to 120 seconds, and the rotation speed is 2200 to 2500 r / min; the defoaming time is 90 to 120 seconds, and the rotation speed is 2000 to 2200 r / min; one mixing and stirring and one defoaming stirring are recorded as one cycle, and the number of cycles is 5 to 10.
[0036] The present invention also provides a liquid metal fiber prepared by the preparation method as described in any one of the above items, wherein the liquid metal fiber has a core-sheath structure, wherein the sheath layer is composed of a polymer elastomer I, and the core layer is composed of liquid metal, a solid conductive substance, and a polymer elastomer II;
[0037] There are multiple pores in the polymer elastomer II, some of which are interconnected to form a network structure, and the remaining pores are not connected to other pores;
[0038] The liquid metal is divided into three parts, which are respectively recorded as liquid metal I, liquid metal II and liquid metal III; liquid metal I is located in the pores of the network structure to form a conductive network, liquid metal II is located on the pore walls of the pores of the network structure and is connected to the conductive network, and liquid metal III is located in the pores that are not connected to form a network structure and is not connected to the conductive network;
[0039] The solid conductive material is divided into three parts, which are respectively denoted as solid conductive material I, solid conductive material II and solid conductive material III; solid conductive material I is located in the pores of the network structure and is connected to the conductive network, solid conductive material II is located on the pore walls of the pores in the network structure and is connected to the conductive network, and solid conductive material III is located in the pores that are not connected to form a network structure and is not connected to the conductive network.
[0040] The polymer elastomer I and the polymer elastomer II exist in the form of solid particles. In the preparation process of the liquid metal fiber, an organic solvent is required to dissolve them. The polymer elastomer I is added to the organic solvent I to obtain a spinning solution I. The liquid metal, the solid conductive material and the polymer elastomer II are added to the organic solvent II to obtain a spinning solution II.
[0041] Spinning solution I is used as the outer spinning solution, and spinning solution II is used as the inner spinning solution, and then the two are added to the syringe respectively, and the spinning solution I and spinning solution II are pushed into the coagulation bath through the coaxial needle; in the coagulation bath process, the organic solvent I in the spinning solution I and the organic solvent II in the spinning solution II will diffuse and exchange with the non-solvent in the coagulation bath, and part of the organic solvent I in the spinning solution I and part of the organic solvent II in the spinning solution II are replaced, reducing the content of organic solvent I in the spinning solution I and organic solvent II in the spinning solution II, promoting the precipitation of polymer elastomer I and polymer elastomer II and forming a solid fiber structure. The subsequent annealing work evaporates the organic solvent I, organic solvent II and non-solvent in the fiber in the form of high temperature, so the final fiber has pores inside, and most of the pores are interconnected, which forms a polymer elastomer I network and a polymer elastomer II network;
[0042] When polymer elastomer II precipitates to form a polymer elastomer II network, part of the liquid metal and solid conductive material will be in the connected pores. Under the synergistic effect of the solid conductive material and the liquid metal, the part of the liquid metal forms a conductive network, and some liquid metal and solid conductive material will adhere to the walls of the connected pores, and some liquid metal and solid conductive material will be wrapped by polymer elastomer II and not connected to the conductive network; the reason why most of the liquid metal and solid conductive material are in the connected pores is that in the coagulation bath, polymer elastomer II precipitates and wraps liquid metal, solid conductive material, solvent and non-solvent. When the organic solvent II and non-solvent evaporate at high temperature, the space where the liquid metal, solid conductive material, solvent and non-solvent are located becomes larger, thereby forming pores. Some pores are interconnected to form a polymer elastomer II network, and some pores exist alone and are not connected to other pores;
[0043] The annealing step in the preparation method can also shrink and solidify the polymer elastomer I network and the polymer elastomer II network.
[0044] As the preferred technical solution:
[0045] The liquid metal fiber as described above has a breaking elongation of 1653-1876%, a tensile strength of 5.7-12.9N, no liquid metal leakage occurs when stretched by 150%, an elastic recovery rate of 86-97% when stretched by 150%, a strain resistance stability of 47-96% when stretched by 150%, and a strain resistance cyclic stability of 2.57-6.13% when stretched by 100%.
[0046] Principle of the invention:
[0047] Liquid metal has low viscosity and high surface tension. It is in liquid state and is easy to flow and diffuse under the action of external force. This high fluidity is the main reason for the leakage of liquid metal in the liquid metal fiber of the prior art. In addition, although the liquid metal in the liquid metal fiber of the prior art has good conductivity, its high fluidity makes the conductivity unstable. The unstable conductivity means that the liquid metal has extremely strong fluidity. When it flows and gathers in one place, the conductivity of that place will be better, but the conductivity of other places with less liquid metal will be poor.
[0048] The liquid metal fiber prepared by the present invention is a core-sheath fiber, wherein the sheath layer of the core-sheath fiber is composed of a polymer elastomer I, and the core layer is composed of liquid metal, a solid conductive material and a polymer elastomer II. After the polymer elastomer II is mixed with the liquid metal, the overall viscosity and adhesion of the system can be significantly improved, and the fluidity of the liquid metal can be slowed down; and during the mixing process, the polymer elastomer II can form a certain degree of physical coating or network structure with the liquid metal, and this structure can limit the free flow of the liquid metal, making the liquid metal more stable in the fiber.
[0049] The fluidity of the spinning solution can be controlled by adjusting the proportion of the polymer elastomer II in the core layer spinning solution. By increasing the proportion of the polymer elastomer II in the spinning solution, the viscosity of the mixture can be further increased, thereby enhancing the ability to control the fluidity of the liquid metal.
[0050] Since the conductivity of liquid metal mainly depends on its continuity, if the liquid metal is dispersed into isolated non-conductive areas, the conductivity of the overall material will be significantly reduced. During the preparation of spinning solution II, the liquid metal exists in the form of tiny droplets or dispersed phases in the spinning solution II. If the proportion of polymer elastomer II is high, polymer elastomer II will wrap the liquid metal to form a composite phase, making it impossible for the liquid metal in the liquid metal fiber core layer to be evenly distributed in polymer elastomer II and unable to form a conductive network structure; in addition, liquid metal has a high surface tension and is easy to form isolated small balls or drop-like structures in the polymer matrix, which will also make it impossible for the liquid metal to effectively connect to form a conductive network.
[0051] Adding polymer elastomer II to spinning solution II solves the problem of leakage caused by high flow of liquid metal and solves the problem of unstable conductivity. Although the conductivity will not be significantly reduced within the range of the addition amount of the present invention, the conductivity is still reduced compared with that without adding polymer elastomer II.
[0052] Adding solid conductive substances to polymers can increase conductivity. However, in the prior art, when solid conductive substances are added to polymers, the contact points between the solid conductive substances may separate during the stretching or bending of the polymer, resulting in interruption of the conductive path, thereby causing unstable conductivity. Therefore, in the case of stretching, those skilled in the art will also believe that mixing solid conductive substances into the polymer elastomer II of the present invention cannot improve the conductivity of the liquid metal fiber.
[0053] However, the present invention has found in experiments that liquid metal and solid conductive material have a synergistic effect. In the case of stretching, mixing solid conductive material into the polymer elastomer II of the present invention can further prevent the leakage of liquid metal in the fiber while improving the conductivity of the liquid metal fiber, which has an unexpected technical effect. The specific analysis is as follows:
[0054] Due to its solid-state characteristics, the solid conductive material in the polymer elastomer II can only provide a preliminary conductive path in the microstructure when doped in small amounts. During the stretching process, the spacing between the solid conductive materials in the prior art increases, which makes the conductive effect worse. In the technical solution of the present invention, the solid conductive material can be adsorbed on the surface of the liquid metal, change the surface energy distribution of the liquid metal, reduce the surface tension, make the liquid metal more easily dispersed in the polymer matrix, and reduce the formation of small balls or drop-like structures; the solid conductive material is distributed on the surface or interface of the liquid metal to form a structure similar to a physical barrier. This barrier limits the liquid metal particles from further shrinking into a spherical shape, helps to extend its shape or maintain an irregular shape, so that the liquid metal is effectively connected to form a conductive network, and the conductive performance is significantly improved.
[0055] In addition, adding solid conductive material to liquid metal can further reduce the fluidity of liquid metal and better fix the liquid metal in its initial position, thereby avoiding leakage; the initial position refers to the initial distribution position of the liquid metal in the polymer elastomer II, which is generally the area formed during the preparation process.
[0056] Liquid metal exhibits excellent "dynamic adaptability" ability during the stretching process. When the liquid metal fiber is subjected to external force, the liquid metal can adjust its distribution in the core layer of the liquid metal fiber, reduce the damage of the external force to the fiber's conductive function, and realize the spontaneous repair of the micro-damage of the core layer caused by the external force, thereby ensuring the long-term stability of the material. Specifically, the liquid metal is confined in the core layer pores formed by the polymer elastomer, which provides a distribution space for the liquid metal that will be restricted and controlled. When the fiber is stretched, the cross-sectional area of the core layer pores is reduced, thereby further compressing the position of the liquid metal, limiting the flow range of the liquid metal, making the fiber more stable and reducing the risk of leakage. In addition, since the liquid metal is fluid, when the core layer of the fiber is broken or voided during the stretching process, the liquid metal will be redistributed to the damaged area, filling the cracks or gaps, and realizing the self-repair function. As the external force is released, the liquid metal returns to its initial position under the action of surface tension (the solid conductive material only reduces the tension of the liquid metal, and does not completely eliminate the tension), and restores its original distribution state. This dynamic adjustment mechanism effectively enhances the mechanical and conductive properties of the material, ensuring its stability and reliability under complex loading conditions.
[0057] During the wet spinning process, the spinning solution can be quickly solidified into fibers through a coagulation bath. The continuous phase formed by the polymer elastomer I of the sheath layer during the coagulation process can effectively cover the core layer, further reducing the risk of liquid metal leakage. In addition, the fiber structure formed after spinning confines the liquid metal in the continuous fiber core layer on a microscopic scale, providing a natural encapsulation effect. This encapsulation avoids additional sealing processes, making the fiber lighter and more flexible.
[0058] By regulating the doping ratio of liquid metal and solid conductive material in the core layer, it is possible to ensure a balance between the stretchability, conductivity and leakage possibility of the liquid metal fiber. In the technical solution of the present invention, based on the total mass of liquid metal, solid conductive material and polymer elastomer II, the mass proportion of solid conductive material is 1-7%, and the mass proportion of polymer elastomer II is 5-11%; when the content of polymer elastomer II is higher than the specified range, the fiber conductivity will be poor; when the content of polymer elastomer II is lower than the specified range, the spinnability of the fiber core layer will be challenged; when the liquid metal content is higher than the specified range, the liquid metal fluidity of the fiber core layer is too strong, which may easily cause the leakage of liquid metal; when the liquid metal content is lower than the specified range, the core layer conductive network is broken when the fiber is stretched, and the liquid metal cannot be redistributed in time, resulting in the destruction of the fiber conductivity; when the content of solid conductive material is higher than the specified range, it is easy to agglomerate in polymer elastomer II to form isolated particle clusters, and the flexibility and elasticity of the fiber will be significantly reduced; when the content of solid conductive material is lower than the specified range, the increase in the fiber conductivity is not obvious. Specifically, in the prior art, when solid conductive materials are added to high polymer elastomers, the solid conductive materials are prone to agglomeration to form isolated particle clusters rather than being evenly distributed in the matrix, which results in an inability to form a continuous conductive network between the particles, thereby affecting the overall conductivity. The present invention solves this problem by utilizing the fluidity of liquid metal within the addition range set by the present invention to evenly disperse the solid conductive materials, thereby preventing the solid conductive materials from forming isolated particle clusters.
[0059] Beneficial effects:
[0060] (1) A liquid metal fiber based on wet spinning of the present invention has excellent stretch-recovery stability and stretch-conductivity stability. The fiber can maintain the stability of its shape and performance during repeated stretching and relaxation, and the conductivity is not significantly affected by mechanical deformation;
[0061] (2) The liquid metal fiber based on wet spinning of the present invention has no liquid metal leakage and is safe and reliable: through unique design and process, the fluidity of the liquid metal is controlled and the liquid metal is always effectively coated to avoid leakage risks, thereby improving the safety and environmental adaptability of the material;
[0062] (3) A method for preparing liquid metal fibers based on wet spinning of the present invention has excellent spinnability and can be prepared continuously: wet spinning realizes efficient compatibility between liquid metal and matrix material, supports a stable process, and has high yield and process scalability;
[0063] (4) The present invention provides a preparation method based on liquid metal fibers. By simultaneously adding liquid metal and solid conductive material to the spinning solution of the functional conductive core layer, the technical problem that a single component is difficult to simultaneously meet both electrical conductivity and stretchability is solved. If only liquid metal is added, the high fluidity will lead to unstable conductivity, and if only solid conductive material is added, the stretchability requirement cannot be met. However, by mixing liquid metal and solid conductive material in a reasonable proportion, both electrical conductivity and stretchability can be achieved, and liquid metal leakage can be effectively prevented, providing important technical support and innovative ideas for the application of liquid metal in flexible electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 A schematic cross-sectional view of a liquid metal fiber prepared by the present invention based on wet spinning;
[0065] Figure 2 A conceptual schematic diagram of a liquid metal fiber based on wet spinning prepared by the present invention;
[0066] Figure 3 This is a conceptual diagram of the cross section of the core layer of a liquid metal fiber based on wet spinning prepared by the present invention;
[0067] Figure 4 The figure is a comparison diagram of the resistance stability performance of fiber a, fiber b, fiber c and fiber d under different strains; wherein fiber c is the liquid metal fiber prepared in Example 1; the difference between fiber a, fiber b and fiber d and fiber c is that the content of polymer elastomer II and liquid metal is different when the mass of the core layer remains unchanged;
[0068] Figure 5 This is a diagram of the conduction stability of a liquid metal fiber based on wet spinning connected to a LED lamp series circuit prepared in Example 1 of the present invention;
[0069] Figure 6 This is a scanning electron microscope (SEM) surface image of a liquid metal fiber based on wet spinning obtained in Example 2 of the present invention after stretching recovery; wherein (a) is a surface image of a fiber sheath layer, and (b) is an enlarged surface image of a local fiber sheath layer;
[0070] Figure 7 This is a scanning electron microscope (SEM) cross-sectional view of a liquid metal fiber based on wet spinning obtained in Example 3 of the present invention after stretching recovery; wherein (c) is a cross-sectional view of the fiber after stretching recovery, and (d) is an enlarged cross-sectional view of the core layer after stretching recovery;
[0071] Among them, 1-sheath, 2-core layer, 3-liquid metal, 4-solid conductive material, 5-polymer elastomer II. DETAILED DESCRIPTION
[0072] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the present invention.
[0073] The test standards / test methods used in the present invention are as follows:
[0074] Elongation at break and tensile strength: At room temperature, the elongation at break and tensile strength of the fiber were tested using an Instron 5965 universal testing machine at a stretching speed of 50 mm / min.
[0075] Elastic recovery rate when stretched by 150%: The elastic recovery performance of the fiber is tested using a multifilament spandex elasticity tester. The stretching speed is 400 mm / min, the load action time is 30 s, the deformation recovery time after load removal is 30 s, and the elastic recovery performance is tested when the strain is 150%.
[0076] Leakage characterization: The surface and cross section of the liquid metal fiber were observed using an S-4800 scanning electron microscope to see if there was any leakage or overflow of the liquid metal. The voltage of the SEM used was 5 kV.
[0077] Stability of strain resistance when stretched by 150%: At room temperature, the liquid metal fiber was tested for strain resistance stability using a transverse stretching machine and a DMM6500 digital multimeter, with a fixed strain of 150% and a stretching frequency of 1000 Hz. The strain resistance stability is expressed by ΔR / R0, where ΔR is the change in resistance before and after stretching, and R0 is the original resistance value before stretching.
[0078] Cyclic stability of strain resistance when stretched by 100%: At room temperature, a lateral stretching machine and a DMM6500 digital multimeter were used to test the cyclic stability of the strain resistance of the liquid metal fiber, wherein the fixed strain was 100%, the cycle was 50 times, and the stretching frequency was 1000Hz; the cyclic stability of the strain resistance was expressed by the drift rate, drift rate = (resistance after stretching in the 50th cycle - initial resistance) / initial resistance * 100%; wherein the initial resistance refers to the resistance before stretching;
[0079] The sources of some substances of the present invention are as follows:
[0080] SEBS: Manufacturer: Shanghai Susheng Plastic Chemical Co., Ltd., brand: G1701.
[0081] TPU: Manufacturer: Covestro Polymer Co., Ltd., brand: 385S.
[0082] TPPE: Manufacturer: Dongguan Fengda Plastic Raw Materials Co., Ltd., brand number: 4556.
[0083] Thermoplastic silicone elastomer: Manufacturer: Dongguan Hongtu Plastic Raw Materials Co., Ltd., brand: 9107.
[0084] SBS: Manufacturer: Jinan Xinhaoyuan Chemical Co., Ltd., Brand: 1002.
[0085] In the embodiment of the present invention, when the liquid metal used is a gallium-indium alloy, gallium accounts for 75.5wt% and indium accounts for 24.5wt%; when the liquid metal is a gallium-indium-tin alloy, gallium accounts for 68.5wt%, indium accounts for 21.5wt% and tin accounts for 10wt%.
[0086] Example 1
[0087] A method for preparing liquid metal fiber, the specific steps are as follows:
[0088] (1) Preparation of raw materials:
[0089] Polymer elastomer I: TPU;
[0090] Organic solvent I: DMF;
[0091] Organic solvent III: DMF;
[0092] Polymer elastomer II: TPU;
[0093] Organic solvent II: DMF;
[0094] Liquid metal: Gallium-Indium alloy;
[0095] Solid conductive material: copper nanoparticles, particle size 1 μm;
[0096] Coagulation bath: water and ethanol in a volume ratio of 5:1;
[0097] (2) preparing spinning solution I;
[0098] Adding polymer elastomer I into organic solvent I and stirring until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 25:100;
[0099] (3) Pulverization of liquid metal;
[0100] The liquid metal is added to the organic solvent III to obtain a mixed solution, and the mixed solution is ultrasonically treated for 60 minutes using an ultrasonic cell crusher, and then the organic solvent III in the mixed solution after ultrasonic treatment is removed and the liquid metal after ultrasonic treatment is retained, and the liquid metal after ultrasonic treatment is placed in a vacuum oven at 120° C. for 12 hours; the mass volume ratio of the liquid metal to the organic solvent III is 100 mg:1 mL;
[0101] (4) preparing spinning solution II;
[0102] Adding polymer elastomer II to organic solvent II, stirring until polymer elastomer II is completely dissolved to obtain solution A, then adding liquid metal and solid conductive material after pulverization to solution A, and then mixing and stirring and defoaming stirring in sequence to obtain spinning solution II;
[0103] Among them, based on the total mass of liquid metal, solid conductive material and polymer elastomer II, the mass proportion of solid conductive material is 5%, and the mass proportion of polymer elastomer II is 9%; the mass volume ratio of polymer elastomer II to organic solvent II is 300 mg:1 mL; the mixing and stirring time is 100 s, and the speed is 2300 r / min; the defoaming time is 100 s, and the speed is 2100 r / min; one mixing and stirring and one defoaming stirring are recorded as one cycle, and the number of cycles is 8;
[0104] (5) Liquid metal fibers are produced by coaxial wet spinning process;
[0105] Spinning solution I is used as the outer spinning solution, and spinning solution II is used as the inner spinning solution, and then the two are added into a syringe respectively, and the spinning solution I and the spinning solution II are pushed into a coagulation bath through a coaxial needle to obtain primary fibers, and the primary fibers are sequentially drawn and wound to obtain core-sheath fibers, and finally the core-sheath fibers are heat-insulated and annealed to obtain liquid metal fibers;
[0106] The propulsion speed of the spinning solution I is 300 μm / min, and the propulsion speed of the spinning solution II is 60 μm / min; the draft ratio is 2:1; the annealing temperature is 60° C., and the annealing time is 12 h.
[0107] like Figures 1 to 3As shown, the liquid metal fiber finally obtained has a core-sheath structure, the sheath layer 1 is composed of a polymer elastomer I, and the core layer 2 is composed of liquid metal 3, a solid conductive substance 4 and a polymer elastomer II; there are multiple channels in the polymer elastomer II, some of which are interconnected to form a network structure, and the remaining channels are not connected to other channels; the liquid metal 3 is divided into three parts, respectively recorded as liquid metal I, liquid metal II and liquid metal III; the liquid metal I is located in the channel of the network structure to form a conductive network, the liquid metal II is located on the pore wall of the channel of the network structure and is connected to the conductive network, and the liquid metal III is located in the channel that is not connected to form a network structure and is not connected to the conductive network; the solid conductive substance 4 is divided into three parts, respectively recorded as solid conductive substance I, solid conductive substance II and solid conductive substance III; the solid conductive substance I is located in the channel of the network structure and is connected to the conductive network, the solid conductive substance II is located on the pore wall of the channel in the network structure and is connected to the conductive network, and the solid conductive substance III is located in the channel that is not connected to form a network structure and is not connected to the conductive network;
[0108] The breaking elongation of the liquid metal fiber is 1653%, the tensile strength is 10.4N, there is no liquid metal leakage when stretched by 150%, the elastic recovery rate is 93% when stretched by 150%, the strain resistance stability is 81% when stretched by 150%, and the strain resistance cyclic stability is 4.26% when stretched by 100%.
[0109] like Figure 5 As shown, there is a resistance change value of about 10Ω from the initial to 100% stretching, which proves the strain resistance stability of the fiber; the fiber is cyclically stretched under 100% strain, and it is found that the resistance change is basically stable, indicating that the liquid metal fiber strain resistance has good cyclic stability;
[0110] like Figure 4As shown, based on Example 1, the influence of different contents of polymer elastomer II in the core layer on the strain resistance stability of the fiber is explored; wherein, the overall mass of the core layer remains unchanged, and when the content of polymer elastomer II changes, the mass of the solid conductive material in the core layer remains unchanged, and the mass of the liquid metal is adjusted accordingly with the mass of polymer elastomer II. When the content of polymer elastomer II in the core layer is 5wt%, it is a fiber; when the content of polymer elastomer II in the core layer is 7wt%, it is b fiber; when the content of polymer elastomer II in the core layer is 9wt%, it is c fiber (i.e., the liquid metal fiber of Example 1); when the content of polymer elastomer II in the core layer is 11wt%, it is d fiber; under different strains, the resistance stability of a fiber, b fiber, c fiber and d fiber is compared, and when the strain is 50%, the resistance change rate of b fiber is the smallest and the stability is the best; there is a difference at 100-200% strain, and the resistance change rate of the liquid metal fiber of Example 1 is smaller. Therefore, in overall comparison, the fiber at 7wt% and 9wt% concentrations showed better stability. The resistance change rate of fiber a was large under different strains, which may be due to the high content of liquid metal in the core layer, causing the cross section of the conductive circuit to basically fit the inner edge of the sheath layer. When stretched, the fiber cross section becomes smaller, which has a greater impact on the cross section of the core layer path, so the resistance change rate is large; the content of liquid metal in fiber d is the least, and the strain resistance change rate is large, which may be caused by the instability of the path due to the low content of liquid metal in the core layer.
[0111] Example 2
[0112] A method for preparing liquid metal fiber, the specific steps are as follows:
[0113] (1) Preparation of raw materials:
[0114] Polymer elastomer I: TPU;
[0115] Organic solvent I: toluene and isopropanol in a volume ratio of 7:3;
[0116] Organic solvent III: toluene and isopropanol in a volume ratio of 7:3;
[0117] Polymer elastomer II: TPU;
[0118] Organic solvent II: toluene and isopropanol in a volume ratio of 7:3;
[0119] Liquid metal: Gallium-Indium alloy;
[0120] Solid conductive material: copper nanowire, 20nm in diameter, 2μm in length;
[0121] Coagulation bath: water and ethanol in a volume ratio of 5:1;
[0122] (2) preparing spinning solution I;
[0123] Adding polymer elastomer I into organic solvent I and stirring until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 25:100;
[0124] (3) Pulverization of liquid metal;
[0125] The liquid metal is added to the organic solvent III to obtain a mixed solution, and the mixed solution is ultrasonically treated for 60 minutes using an ultrasonic cell crusher, and then the organic solvent III in the mixed solution after ultrasonic treatment is removed and the liquid metal after ultrasonic treatment is retained, and the liquid metal after ultrasonic treatment is placed in a vacuum oven at 120° C. for 12 hours; the mass volume ratio of the liquid metal to the organic solvent III is 100 mg:1 mL;
[0126] (4) preparing spinning solution II;
[0127] Adding polymer elastomer II to organic solvent II, stirring until polymer elastomer II is completely dissolved to obtain solution A, then adding liquid metal and solid conductive material after pulverization to solution A, and then mixing and stirring and defoaming stirring in sequence to obtain spinning solution II;
[0128] Among them, based on the total mass of liquid metal, solid conductive material and polymer elastomer II, the mass proportion of solid conductive material is 7%, and the mass proportion of polymer elastomer II is 7%; the mass volume ratio of polymer elastomer II to organic solvent II is 200 mg:1 mL; the mixing and stirring time is 90 s, and the speed is 2200 r / min; the defoaming time is 90 s, and the speed is 2000 r / min; one mixing and stirring and one defoaming stirring are recorded as one cycle, and the number of cycles is 5;
[0129] (5) Liquid metal fibers are produced by coaxial wet spinning process;
[0130] Spinning solution I is used as the outer spinning solution, and spinning solution II is used as the inner spinning solution, and then the two are added into a syringe respectively, and the spinning solution I and the spinning solution II are pushed into a coagulation bath through a coaxial needle to obtain primary fibers, and the primary fibers are sequentially drawn and wound to obtain core-sheath fibers, and finally the core-sheath fibers are heat-insulated and annealed to obtain liquid metal fibers;
[0131] The propulsion speed of the spinning solution I is 400 μm / min, and the propulsion speed of the spinning solution II is 150 μm / min; the draft ratio is 5:1; the annealing temperature is 80° C., and the annealing time is 8 h.
[0132] The finally obtained liquid metal fiber has a core-sheath structure, the sheath layer is composed of a polymer elastomer I, and the core layer is composed of liquid metal, a solid conductive substance and a polymer elastomer II; there are multiple channels in the polymer elastomer II, some of which are interconnected to form a network structure, and the remaining channels are not connected to other channels; the liquid metal is divided into three parts, respectively recorded as liquid metal I, liquid metal II and liquid metal III; the liquid metal I is located in the channels of the network structure to form a conductive network, the liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and the liquid metal III is located in the channels that are not connected to form a network structure and is not connected to the conductive network; the solid conductive substance is divided into three parts, respectively recorded as solid conductive substance I, solid conductive substance II and solid conductive substance III; the solid conductive substance I is located in the channels of the network structure and is connected to the conductive network, the solid conductive substance II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and the solid conductive substance III is located in the channels that are not connected to form a network structure and is not connected to the conductive network;
[0133] The breaking elongation of the liquid metal fiber is 1703%, the tensile strength is 5.7N, there is no liquid metal leakage when stretched by 150%, the elastic recovery rate is 86% when stretched by 150%, the strain resistance stability is 57% when stretched by 150%, and the strain resistance cyclic stability is 2.78% when stretched by 100%.
[0134] like Figure 6 As shown, the fiber surface is a closed groove structure, the surface structure is uniform and seamless, and there is no tendency of liquid metal leakage, which proves the integrity of the sheath-core structure wrapping.
[0135] Example 3
[0136] A method for preparing liquid metal fiber, the specific steps are as follows:
[0137] (1) Preparation of raw materials:
[0138] Polymer elastomer I: TPU;
[0139] Organic solvent I: DMSO;
[0140] Organic solvent III: DMSO;
[0141] Polymer elastomer II: SEBS;
[0142] Organic solvent II: DMSO;
[0143] Liquid metal: Gallium-Indium alloy;
[0144] Solid conductive material: silver nanoparticles, particle size 1 μm;
[0145] Coagulation bath: water and ethanol in a volume ratio of 5:1;
[0146] (2) preparing spinning solution I;
[0147] Adding polymer elastomer I into organic solvent I and stirring until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 35:100;
[0148] (3) Pulverization of liquid metal;
[0149] The liquid metal is added to the organic solvent III to obtain a mixed solution, and the mixed solution is ultrasonically treated for 60 minutes using an ultrasonic cell crusher, and then the organic solvent III in the mixed solution after ultrasonic treatment is removed and the liquid metal after ultrasonic treatment is retained, and the liquid metal after ultrasonic treatment is placed in a vacuum oven at 120° C. for 12 hours; the mass volume ratio of the liquid metal to the organic solvent III is 100 mg:1 mL;
[0150] (4) preparing spinning solution II;
[0151] Adding polymer elastomer II to organic solvent II, stirring until polymer elastomer II is completely dissolved to obtain solution A, then adding liquid metal and solid conductive material after pulverization to solution A, and then mixing and stirring and defoaming stirring in sequence to obtain spinning solution II;
[0152] Among them, based on the total mass of liquid metal, solid conductive material and polymer elastomer II, the mass proportion of solid conductive material is 1%, and the mass proportion of polymer elastomer II is 9%; the mass volume ratio of polymer elastomer II to organic solvent II is 400 mg:1 mL; the mixing and stirring time is 120 s, and the speed is 2500 r / min; the defoaming time is 120 s, and the speed is 2200 r / min; one mixing and stirring and one defoaming stirring are recorded as one cycle, and the number of cycles is 10;
[0153] (5) Liquid metal fibers are produced by coaxial wet spinning process;
[0154] Spinning solution I is used as the outer spinning solution, and spinning solution II is used as the inner spinning solution, and then the two are added into a syringe respectively, and the spinning solution I and the spinning solution II are pushed into a coagulation bath through a coaxial needle to obtain primary fibers, and the primary fibers are sequentially drawn and wound to obtain core-sheath fibers, and finally the core-sheath fibers are heat-insulated and annealed to obtain liquid metal fibers;
[0155] The propulsion speed of the spinning solution I is 250 μm / min, and the propulsion speed of the spinning solution II is 100 μm / min; the draft ratio is 1:1; the annealing temperature is 50° C., and the annealing time is 15 h.
[0156] The finally obtained liquid metal fiber has a core-sheath structure, the sheath layer is composed of a polymer elastomer I, and the core layer is composed of liquid metal, a solid conductive substance and a polymer elastomer II; there are multiple channels in the polymer elastomer II, some of which are interconnected to form a network structure, and the remaining channels are not connected to other channels; the liquid metal is divided into three parts, respectively recorded as liquid metal I, liquid metal II and liquid metal III; the liquid metal I is located in the channels of the network structure to form a conductive network, the liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and the liquid metal III is located in the channels that are not connected to form a network structure and is not connected to the conductive network; the solid conductive substance is divided into three parts, respectively recorded as solid conductive substance I, solid conductive substance II and solid conductive substance III; the solid conductive substance I is located in the channels of the network structure and is connected to the conductive network, the solid conductive substance II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and the solid conductive substance III is located in the channels that are not connected to form a network structure and is not connected to the conductive network;
[0157] The breaking elongation of the liquid metal fiber is 1876%, the tensile strength is 12.9N, there is no liquid metal leakage when stretched by 150%, the elastic recovery rate is 96% when stretched by 150%, the strain resistance stability is 96% when stretched by 150%, and the strain resistance cyclic stability is 6.13% when stretched by 100%.
[0158] In such Figure 7 In the cross-sectional view shown in (c), it can be seen that the core layer is completely wrapped by the sheath layer without leakage; Figure 7 In the partial enlarged image shown in (d), it can be seen that the dispersed liquid metal 3 is wrapped by the polymer elastomer II 5, and some of the surfaces are attached with solid conductive materials 4. It is proved that the sheath-core structure and the core layer doping can effectively improve the fluidity of the liquid metal, thereby reducing the possibility of liquid metal leakage.
[0159] Example 4
[0160] A method for preparing liquid metal fiber, the specific steps are as follows:
[0161] (1) Preparation of raw materials:
[0162] Polymer elastomer I: SEBS;
[0163] Organic solvent I: toluene;
[0164] Organic solvent III: toluene;
[0165] Polymer elastomer II: SEBS;
[0166] Organic solvent II: toluene;
[0167] Liquid metal: Gallium-Indium alloy;
[0168] Solid conductive material: carbon nanotubes, 2nm in diameter and 5μm in length;
[0169] Coagulation bath: water and isopropanol in a volume ratio of 5:1;
[0170] (2) preparing spinning solution I;
[0171] Adding polymer elastomer I into organic solvent I and stirring until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 25:100;
[0172] (3) Pulverization of liquid metal;
[0173] The liquid metal is added to the organic solvent III to obtain a mixed solution, and the mixed solution is ultrasonically treated for 60 minutes using an ultrasonic cell crusher, and then the organic solvent III in the mixed solution after ultrasonic treatment is removed and the liquid metal after ultrasonic treatment is retained, and the liquid metal after ultrasonic treatment is placed in a vacuum oven at 120° C. for 12 hours; the mass volume ratio of the liquid metal to the organic solvent III is 100 mg:1 mL;
[0174] (4) preparing spinning solution II;
[0175] Adding polymer elastomer II to organic solvent II, stirring until polymer elastomer II is completely dissolved to obtain solution A, then adding liquid metal and solid conductive material after pulverization to solution A, and then mixing and stirring and defoaming stirring in sequence to obtain spinning solution II;
[0176] Among them, based on the total mass of liquid metal, solid conductive material and polymer elastomer II, the mass proportion of solid conductive material is 3%, and the mass proportion of polymer elastomer II is 11%; the mass volume ratio of polymer elastomer II to organic solvent II is 300 mg:1 mL; the mixing and stirring time is 110 s, and the speed is 2200 r / min; the defoaming time is 110 s, and the speed is 2000 r / min; one mixing and stirring and one defoaming stirring are recorded as one cycle, and the number of cycles is 7;
[0177] (5) Liquid metal fibers are produced by coaxial wet spinning process;
[0178] Spinning solution I is used as the outer spinning solution, and spinning solution II is used as the inner spinning solution, and then the two are added into a syringe respectively, and the spinning solution I and the spinning solution II are pushed into a coagulation bath through a coaxial needle to obtain primary fibers, and the primary fibers are sequentially drawn and wound to obtain core-sheath fibers, and finally the core-sheath fibers are heat-insulated and annealed to obtain liquid metal fibers;
[0179] The propulsion speed of the spinning solution I is 300 μm / min, and the propulsion speed of the spinning solution II is 120 μm / min; the draft ratio is 3:1; the annealing temperature is 60° C., and the annealing time is 10 h.
[0180] The finally obtained liquid metal fiber has a core-sheath structure, the sheath layer is composed of a polymer elastomer I, and the core layer is composed of liquid metal, a solid conductive substance and a polymer elastomer II; there are multiple channels in the polymer elastomer II, some of which are interconnected to form a network structure, and the remaining channels are not connected to other channels; the liquid metal is divided into three parts, respectively recorded as liquid metal I, liquid metal II and liquid metal III; the liquid metal I is located in the channels of the network structure to form a conductive network, the liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and the liquid metal III is located in the channels that are not connected to form a network structure and is not connected to the conductive network; the solid conductive substance is divided into three parts, respectively recorded as solid conductive substance I, solid conductive substance II and solid conductive substance III; the solid conductive substance I is located in the channels of the network structure and is connected to the conductive network, the solid conductive substance II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and the solid conductive substance III is located in the channels that are not connected to form a network structure and is not connected to the conductive network;
[0181] The breaking elongation of the liquid metal fiber is 1849%, the tensile strength is 8.3N, there is no liquid metal leakage when stretched by 150%, the elastic recovery rate is 97% when stretched by 150%, the strain resistance stability is 47% when stretched by 150%, and the strain resistance cyclic stability is 2.57% when stretched by 100%.
[0182] Example 5
[0183] A method for preparing liquid metal fiber, the specific steps are as follows:
[0184] (1) Preparation of raw materials:
[0185] Polymer elastomer I: SBS;
[0186] Organic solvent I: toluene and THF in a volume ratio of 6:4;
[0187] Organic solvent III: acetone;
[0188] Polymer elastomer II: Thermoplastic silicone elastomer;
[0189] Organic solvent II: toluene and THF in a volume ratio of 6:4;
[0190] Liquid metal: Gallium;
[0191] Solid conductive material: silver nanosheets, 20 nm thick and 3 μm in lateral dimension;
[0192] Coagulation bath: cyclohexane and brine in a volume ratio of 1:1, the brine being a 5wt% NaCl aqueous solution;
[0193] (2) preparing spinning solution I;
[0194] Adding polymer elastomer I into organic solvent I and stirring until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 20:100;
[0195] (3) Pulverization of liquid metal;
[0196] The liquid metal is added to the organic solvent III to obtain a mixed solution, and the mixed solution is ultrasonically treated for 60 minutes using an ultrasonic cell crusher, and then the organic solvent III in the mixed solution after ultrasonic treatment is removed and the liquid metal after ultrasonic treatment is retained, and the liquid metal after ultrasonic treatment is placed in a vacuum oven at 120° C. for 12 hours; the mass volume ratio of the liquid metal to the organic solvent III is 100 mg:1 mL;
[0197] (4) preparing spinning solution II;
[0198] Adding polymer elastomer II to organic solvent II, stirring until polymer elastomer II is completely dissolved to obtain solution A, then adding liquid metal and solid conductive material after pulverization to solution A, and then mixing and stirring and defoaming stirring in sequence to obtain spinning solution II;
[0199] Among them, based on the total mass of liquid metal, solid conductive material and polymer elastomer II, the mass proportion of solid conductive material is 5%, and the mass proportion of polymer elastomer II is 8%; the mass volume ratio of polymer elastomer II to organic solvent II is 250mg:1mL; the mixing and stirring time is 110s, and the speed is 2400r / min; the defoaming time is 110s, and the speed is 2200r / min; one mixing and stirring and one defoaming stirring are recorded as one cycle, and the number of cycles is 9;
[0200] (5) Liquid metal fibers are produced by coaxial wet spinning process;
[0201] Spinning solution I is used as the outer spinning solution, and spinning solution II is used as the inner spinning solution, and then the two are added into a syringe respectively, and the spinning solution I and the spinning solution II are pushed into a coagulation bath through a coaxial needle to obtain primary fibers, and the primary fibers are sequentially drawn and wound to obtain core-sheath fibers, and finally the core-sheath fibers are heat-insulated and annealed to obtain liquid metal fibers;
[0202] The propulsion speed of the spinning solution I is 350 μm / min, and the propulsion speed of the spinning solution II is 70 μm / min; the draft ratio is 4:1; the annealing temperature is 70° C., and the annealing time is 11 h.
[0203] The finally obtained liquid metal fiber has a core-sheath structure, the sheath layer is composed of a polymer elastomer I, and the core layer is composed of liquid metal, a solid conductive substance and a polymer elastomer II; there are multiple channels in the polymer elastomer II, some of which are interconnected to form a network structure, and the remaining channels are not connected to other channels; the liquid metal is divided into three parts, respectively recorded as liquid metal I, liquid metal II and liquid metal III; the liquid metal I is located in the channels of the network structure to form a conductive network, the liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and the liquid metal III is located in the channels that are not connected to form a network structure and is not connected to the conductive network; the solid conductive substance is divided into three parts, respectively recorded as solid conductive substance I, solid conductive substance II and solid conductive substance III; the solid conductive substance I is located in the channels of the network structure and is connected to the conductive network, the solid conductive substance II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and the solid conductive substance III is located in the channels that are not connected to form a network structure and is not connected to the conductive network;
[0204] The breaking elongation of the liquid metal fiber is 1750%, the tensile strength is 9.5N, there is no liquid metal leakage when stretched by 150%, the elastic recovery rate is 90% when stretched by 150%, the strain resistance stability is 65% when stretched by 150%, and the strain resistance cyclic stability is 3.80% when stretched by 100%.
[0205] Example 6
[0206] A method for preparing liquid metal fiber, the specific steps are as follows:
[0207] (1) Preparation of raw materials:
[0208] Polymer elastomer I: TPPE;
[0209] Organic solvent I: DMAC;
[0210] Organic solvent III: DMAC;
[0211] Polymer elastomer II: TPU;
[0212] Organic solvent II: DMAC;
[0213] Liquid metal: Gallium-Indium-Tin alloy;
[0214] Solid conductive material: copper nanosheets, 20nm thick and 3μm in lateral dimension;
[0215] Coagulation bath: water and methanol in a volume ratio of 5:1;
[0216] (2) preparing spinning solution I;
[0217] Adding polymer elastomer I into organic solvent I and stirring until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 30:100;
[0218] (3) Pulverization of liquid metal;
[0219] The liquid metal is added to the organic solvent III to obtain a mixed solution, and the mixed solution is ultrasonically treated for 60 minutes using an ultrasonic cell crusher, and then the organic solvent III in the mixed solution after ultrasonic treatment is removed and the liquid metal after ultrasonic treatment is retained, and the liquid metal after ultrasonic treatment is placed in a vacuum oven at 120° C. for 12 hours; the mass volume ratio of the liquid metal to the organic solvent III is 100 mg:1 mL;
[0220] (4) preparing spinning solution II;
[0221] Adding polymer elastomer II to organic solvent II, stirring until polymer elastomer II is completely dissolved to obtain solution A, then adding liquid metal and solid conductive material after pulverization to solution A, and then mixing and stirring and defoaming stirring in sequence to obtain spinning solution II;
[0222] Among them, based on the total mass of liquid metal, solid conductive material and polymer elastomer II, the mass proportion of solid conductive material is 6%, and the mass proportion of polymer elastomer II is 6%; the mass volume ratio of polymer elastomer II to organic solvent II is 350mg:1mL; the mixing and stirring time is 100s, and the speed is 2200r / min; the defoaming time is 100s, and the speed is 2000r / min; one mixing and stirring and one defoaming stirring are recorded as one cycle, and the number of cycles is 6;
[0223] (5) Liquid metal fibers are produced by coaxial wet spinning process;
[0224] Spinning solution I is used as the outer spinning solution, and spinning solution II is used as the inner spinning solution, and then the two are added into a syringe respectively, and the spinning solution I and the spinning solution II are pushed into a coagulation bath through a coaxial needle to obtain primary fibers, and the primary fibers are sequentially drawn and wound to obtain core-sheath fibers, and finally the core-sheath fibers are heat-insulated and annealed to obtain liquid metal fibers;
[0225] The propulsion speed of the spinning solution I is 320 μm / min, and the propulsion speed of the spinning solution II is 130 μm / min; the draft ratio is 2:1; the annealing temperature is 60° C., and the annealing time is 12 h.
[0226] The finally obtained liquid metal fiber has a core-sheath structure, the sheath layer is composed of a polymer elastomer I, and the core layer is composed of liquid metal, a solid conductive substance and a polymer elastomer II; there are multiple channels in the polymer elastomer II, some of which are interconnected to form a network structure, and the remaining channels are not connected to other channels; the liquid metal is divided into three parts, respectively recorded as liquid metal I, liquid metal II and liquid metal III; the liquid metal I is located in the channels of the network structure to form a conductive network, the liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and the liquid metal III is located in the channels that are not connected to form a network structure and is not connected to the conductive network; the solid conductive substance is divided into three parts, respectively recorded as solid conductive substance I, solid conductive substance II and solid conductive substance III; the solid conductive substance I is located in the channels of the network structure and is connected to the conductive network, the solid conductive substance II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and the solid conductive substance III is located in the channels that are not connected to form a network structure and is not connected to the conductive network;
[0227] The breaking elongation of the liquid metal fiber is 1685%, the tensile strength is 11.7N, there is no liquid metal leakage when stretched by 150%, the elastic recovery rate is 92% when stretched by 150%, the strain resistance stability is 78% when stretched by 150%, and the strain resistance cyclic stability is 4.02% when stretched by 100%.
[0228] Example 7
[0229] A method for preparing liquid metal fiber, the specific steps are as follows:
[0230] (1) Preparation of raw materials:
[0231] Polymer elastomer I: Thermoplastic silicone elastomer;
[0232] Organic solvent I: THF;
[0233] Organic solvent III: acetone;
[0234] Polymer elastomer II: SEBS;
[0235] Organic solvent II: THF;
[0236] Liquid metal: Gallium-Indium alloy;
[0237] Solid conductive material: copper nanoparticles, particle size 1 μm;
[0238] Coagulation bath: cyclohexane and hexane in a volume ratio of 3:2;
[0239] (2) preparing spinning solution I;
[0240] Adding polymer elastomer I into organic solvent I and stirring until polymer elastomer I is completely dissolved to obtain spinning solution I; the mass ratio of polymer elastomer I to organic solvent I is 25:100;
[0241] (3) Pulverization of liquid metal;
[0242] The liquid metal is added to the organic solvent III to obtain a mixed solution, and the mixed solution is ultrasonically treated for 60 minutes using an ultrasonic cell crusher, and then the organic solvent III in the mixed solution after ultrasonic treatment is removed and the liquid metal after ultrasonic treatment is retained, and the liquid metal after ultrasonic treatment is placed in a vacuum oven at 120° C. for 12 hours; the mass volume ratio of the liquid metal to the organic solvent III is 100 mg:1 mL;
[0243] (4) preparing spinning solution II;
[0244] Adding polymer elastomer II to organic solvent II, stirring until polymer elastomer II is completely dissolved to obtain solution A, then adding liquid metal and solid conductive material after pulverization to solution A, and then mixing and stirring and defoaming stirring in sequence to obtain spinning solution II;
[0245] Among them, based on the total mass of liquid metal, solid conductive material and polymer elastomer II, the mass proportion of solid conductive material is 4%, and the mass proportion of polymer elastomer II is 7%; the mass volume ratio of polymer elastomer II to organic solvent II is 320 mg:1 mL; the mixing and stirring time is 120 s, and the speed is 2300 r / min; the defoaming time is 120 s, and the speed is 2100 r / min; one mixing and stirring and one defoaming stirring are recorded as one cycle, and the number of cycles is 8;
[0246] (5) Liquid metal fibers are produced by coaxial wet spinning process;
[0247] Spinning solution I is used as the outer spinning solution, and spinning solution II is used as the inner spinning solution, and then the two are added into a syringe respectively, and the spinning solution I and the spinning solution II are pushed into a coagulation bath through a coaxial needle to obtain primary fibers, and the primary fibers are sequentially drawn and wound to obtain core-sheath fibers, and finally the core-sheath fibers are heat-insulated and annealed to obtain liquid metal fibers;
[0248] The propulsion speed of the spinning solution I is 380 μm / min, and the propulsion speed of the spinning solution II is 90 μm / min; the draft ratio is 3:1; the annealing temperature is 80° C., and the annealing time is 9 h.
[0249] The finally obtained liquid metal fiber has a core-sheath structure, the sheath layer is composed of a polymer elastomer I, and the core layer is composed of liquid metal, a solid conductive substance and a polymer elastomer II; there are multiple channels in the polymer elastomer II, some of which are interconnected to form a network structure, and the remaining channels are not connected to other channels; the liquid metal is divided into three parts, respectively recorded as liquid metal I, liquid metal II and liquid metal III; the liquid metal I is located in the channels of the network structure to form a conductive network, the liquid metal II is located on the pore walls of the channels of the network structure and is connected to the conductive network, and the liquid metal III is located in the channels that are not connected to form a network structure and is not connected to the conductive network; the solid conductive substance is divided into three parts, respectively recorded as solid conductive substance I, solid conductive substance II and solid conductive substance III; the solid conductive substance I is located in the channels of the network structure and is connected to the conductive network, the solid conductive substance II is located on the pore walls of the channels in the network structure and is connected to the conductive network, and the solid conductive substance III is located in the channels that are not connected to form a network structure and is not connected to the conductive network;
[0250] The breaking elongation of the liquid metal fiber is 1762%, the tensile strength is 10.1N, there is no liquid metal leakage when stretched by 150%, the elastic recovery rate is 94% when stretched by 150%, the strain resistance stability is 71% when stretched by 150%, and the strain resistance cyclic stability is 3.68% when stretched by 100%.
Claims
1. A method for preparing liquid metal fiber, characterized in that: The core-sheath fiber is prepared by wet spinning process, and the liquid metal fiber is obtained after heat preservation annealing; In the core-sheath fiber, the raw material corresponding to the sheath layer is spinning solution I, and the raw material corresponding to the core layer is spinning solution II; The spinning solution I is prepared by adding a polymer elastomer I into an organic solvent I; The spinning solution II is prepared by adding liquid metal, solid conductive material and polymer elastomer II into organic solvent II; Based on the total mass of the liquid metal, the solid conductive material and the polymer elastomer II, the mass of the solid conductive material accounts for 1 to 7%, and the mass of the polymer elastomer II accounts for 5 to 11%; The mass volume ratio of polymer elastomer II to organic solvent II is 200-400 mg:1 mL.
2. The method for preparing a liquid metal fiber according to claim 1, characterized in that: The specific steps of the preparation method are as follows: (1) preparing spinning solution I; Adding a polymer elastomer I into an organic solvent I and stirring until the polymer elastomer I is completely dissolved to obtain a spinning solution I; (2) preparing spinning solution II; Adding polymer elastomer II to organic solvent II, stirring until polymer elastomer II is completely dissolved to obtain solution A, and then adding liquid metal and solid conductive material to solution A to obtain spinning solution II; (3) Liquid metal fibers are produced by coaxial wet spinning process; Spinning solution I is used as the outer spinning solution, and spinning solution II is used as the inner spinning solution, and then the two are added into a syringe respectively, and the spinning solution I and the spinning solution II are pushed into a coagulation bath through a coaxial needle to obtain primary fibers, and the primary fibers are sequentially drawn and wound to obtain core-sheath fibers, and finally the core-sheath fibers are heat-insulated and annealed to obtain liquid metal fibers; The propulsion speed of the spinning solution I is 250-400 μm / min, and the propulsion speed of the spinning solution II is 60-150 μm / min; the draft ratio is 1-5:1; the annealing temperature is 50-80° C., and the annealing time is 8-15 hours.
3. The method for preparing a liquid metal fiber according to claim 2, characterized in that: The liquid metal is one or more of gallium, gallium-indium alloy and gallium-indium-tin alloy; the solid conductive material is one or more of a metal material and a carbon-based material; the metal material is one or more of silver nanoparticles, copper nanoparticles, silver nanowires, copper nanowires, silver nanosheets and copper nanosheets; the carbon-based material is one or more of carbon black, carbon nanotubes and graphene.
4. The method for preparing a liquid metal fiber according to claim 3, characterized in that: The polymer elastomer I and the polymer elastomer II are each independently selected from one or more of acrylonitrile-butadiene-styrene copolymer, styrene-ethylene / butylene-styrene block copolymer, thermoplastic polyurethane, thermoplastic polyester elastomer, thermoplastic silicone elastomer and styrene-butadiene-styrene block copolymer.
5. The method for preparing liquid metal fiber according to claim 4, characterized in that: The organic solvent I and the organic solvent II are independently selected from one or more of acetone, tetrahydrofuran, dimethyl sulfoxide, dimethylformamide, dimethylacetamide and toluene; the coagulation bath is one or more of water, brine, methanol, ethanol, isopropanol, cyclohexane and hexane; and the brine is a 5wt% NaCl aqueous solution.
6. The method for preparing a liquid metal fiber according to claim 5, characterized in that: The mass ratio of the polymer elastomer I to the organic solvent I is 15 to 35:
100.
7. The method for preparing liquid metal fiber according to claim 6, characterized in that: The liquid metal needs to be crushed before being added to solution A. The specific process is: the liquid metal is added to the organic solvent III to obtain a mixed solution, the mixed solution is ultrasonically treated for 40 to 80 minutes using an ultrasonic cell crusher, and then the organic solvent III in the mixed solution after ultrasonic treatment is removed and the liquid metal after ultrasonic treatment is retained, and the liquid metal after ultrasonic treatment is placed in a vacuum oven at 100 to 150° C. for 9 to 15 hours; the organic solvent III is one or more of acetone, tetrahydrofuran, dimethyl sulfoxide, dimethylformamide, dimethylacetamide and toluene.
8. The method for preparing liquid metal fiber according to claim 7, characterized in that: After adding liquid metal and solid conductive material to solution A, mixing and stirring and defoaming stirring are carried out in sequence; the mixing and stirring time is 90 to 120 seconds, and the rotation speed is 2200 to 2500 r / min; the defoaming time is 90 to 120 seconds, and the rotation speed is 2000 to 2200 r / min; one mixing and stirring and one defoaming stirring is recorded as one cycle, and the number of cycles is 5 to 10.
9. The liquid metal fiber obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The liquid metal fiber has a core-sheath structure, the sheath layer is composed of polymer elastomer I, and the core layer is composed of liquid metal, solid conductive material and polymer elastomer II; There are multiple pores in the polymer elastomer II, some of which are interconnected to form a network structure, and the remaining pores are not connected to other pores; The liquid metal is divided into three parts, which are respectively recorded as liquid metal I, liquid metal II and liquid metal III; liquid metal I is located in the pores of the network structure to form a conductive network, liquid metal II is located on the pore walls of the pores of the network structure and is connected to the conductive network, and liquid metal III is located in the pores that are not connected to form a network structure and is not connected to the conductive network; The solid conductive material is divided into three parts, which are respectively denoted as solid conductive material I, solid conductive material II and solid conductive material III; solid conductive material I is located in the pores of the network structure and is connected to the conductive network, solid conductive material II is located on the pore walls of the pores in the network structure and is connected to the conductive network, and solid conductive material III is located in the pores that are not connected to form a network structure and is not connected to the conductive network.
10. The liquid metal fiber according to claim 9, characterized in that: The breaking elongation of the liquid metal fiber is 1653~1876%, the tensile strength is 5.7~12.9N, there is no liquid metal leakage when stretched by 150%, the elastic recovery rate is 86~97% when stretched by 150%, the strain resistance stability is 47~96% when stretched by 150%, and the strain resistance cyclic stability is 2.57~6.13% when stretched by 100%.
Citation Information
Patent Citations
Liquid metal fiber and preparation method and application thereof
CN115464122A
Preparation method and application of self-packaging organic polymer coated liquid metal wire
CN116453774A
Fiber velometer made of liquid metal sensing fiber and application of fiber velometer in intelligent elastic band
CN118007279A
Preparation method and application of high-conductivity and high-stretchability elastomer
CN113990557A
One-step forming batch preparation method of liquid metal conductive fiber with core-shell structure
CN114703555A
Cited By
One-sheath double-core conductive fiber and preparation method and application thereof
CN122128842A